Sumane Bewawo Hasi Ritual: A symbolic act respecting the ancestors in South Nias Regency - Hia, Potensi Juniarti; Zega, Firman Yamonaha (Department of Sociology, Faculty of Social and Political Sciences, Universitas Airlangga, 2021)
Sumane bewawÓ§ hasi is one of the rituals in the funeral ceremony originating from the Nias Tribe that is engaged in by the people in Ó§ri To'ene, Ó§ri MazinÓ§, and Ó§ri Onolalu in South Nias. This study aimed to determine the symbolic meaning of each of the series of rituals to do with the giving of sumane bewawÓ§ hasi. This study used a qualitative descriptive research method and symbolic interaction theory. The data collection in this study consisted of interviews, observations, and documentation techniques. Furthermore, the data analysis used data reduction, data analysis, and drawing conclusions. The result of this research shows that sumane bewawÓ§ hasi is a symbolic act that specifically aims to pay homage to the parents or ancestors as a symbol of separation. It can also involve famolakhÓ§mi ya'ira sofulo (glory/dignity of the community) and appreciation of the people attending the funeral. This ritual also aims to strengthen the kinship in the family (fahasara dÓ§dÓ§ si fatifusÓ§) as a form of togetherness, celebrating the involvement of the entire extended family in the implementation of the religious and familial events. The implementation process consists of several stages: orahua sifatalifusÓ§, fame'e sumane and the implementation of hÓ§lihÓ§li Sumane.